KADAR FIBRIN MONOMER DAN UKURAN INFARK DI STROK ISKEMIK AKUT - Ani Kartini; Mansyur Arif; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Coagulation activation and thrombosis frequently exist in ischemic stroke, thrombus formation can be detected early by the presence of fibrin monomer. The purpose of this study was to know the correlation of fibrin monomer level with cerebral infarct size in acute ischemic stroke patients. This was a cross sectional study with a total of 39 samples. The fibrin monomer level was determined by immunoturbidimetry method using STA-Compact and the measurement of the infarct size was done by CT scan of the head using Broderick formula. The results of this study showed that the median level of fibrin monomer in acute ischemic stroke with nonlacunar infarct type and lacunar infarct type were 14.46 μg/mL and 4.29 μg/mL, respectively. Mann-Whitney test showed there was a significant difference of fibrin monomer levels between nonlacunar infarct type and the lacunar type, p=0.000. The cut-off point analysis result of the fibrin monomer level was 5.96 μg/mL with a sensitivity of 88.9% and specificity of 76.4%, respectively. Spearman correlation test showed that fibrin monomer level was positively correlated with cerebral infarct volume in acute ischemic stroke (r=0.56, p=0.000). Based on this study, it can be concluded that fibrin monomer level can be used as a marker to predict the type of cerebral infarct and volume of acute ischemic stroke as well.